THE INFLUENCE BETWEEN GENDER INTERPERSONAL SKILLS AND HIGHER-ORDER THINKING SKILLS IN HISTORY EDUCATION - Lukitaningsih; Nadya Tridrisna Manurung; Arfan Diansyah; Lister Eva Simangunsong; Mhd. Ihsan S Nasution (Universitas Negeri Medan, 2026)
HOTS learning that includes analysis, evaluation, and creation is a challenge in 21st-century learning. This includes understanding the values of local wisdom to encourage analytical, creative, and evaluative thinking towards complex cultural heritage. In its development, critical and reflective thinking to understand local wisdom is influenced by factors such as gender and interpersonal intelligence. Understanding local wisdom not only requires cognitive abilities but also concerns one's position in society, gender roles, and interpersonal intelligence. Gender influences students' historical perspectives and experiences, while interpersonal intelligence relates to students' experiences in interacting, discussing, and analyzing local values. This study aims to explore the relationship between gender identity and interpersonal intelligence in influencing HOTS thinking in history learning based on local wisdom. Using a quantitative approach with descriptive statistical methods with a population of history students who take local wisdom courses selected through purposive sampling. The results of the study indicate that there is a significant influence of gender on higher-order thinking skills (HOTS), especially in the aspect of critical thinking in learning local wisdom, while in interpersonal intelligence, men and women have equivalent results. In addition, interpersonal intelligence does not significantly affect HOTS abilities. So it can be concluded that strategies that can bridge collaboration between genders will create successful local wisdom learning. Key words: Gender, HOTS, Interpersonal Intelligence, Local Wisdom